Integrative sport medicine rehabilitation for early-onset knee osteoarthritis in overweight young adults: Evidence from meta-analytic reviews - Moch. Yunus; Supriyadi; Gosy Endra Vigriawan; Mahalul Azam; Endang Sri Wahjuni (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Early-onset and early-stage knee osteoarthritis (KOA) is increasingly reported in overweight young adults and is associated with pain, functional limitations, and reduced quality of life. This umbrella review aims to map the domains of Sports Medicine-Oriented Holistic Rehabilitation (SMOHR) interventions, defined as exercise-based therapy combined with at least one additional domain, and to summarize the reported effects and certainty of evidence for pain, physical function, psychosocial outcomes, and quality of life. Methods: A PRISMA 2020-guided search of PubMed, Scopus, Web of Science, and SPORTDiscus identified English-language systematic reviews with meta-analyses and network meta-analyses published between 2021 and 2025. Two reviewers independently screened abstracts and full texts; disagreements were resolved through discussion and review by a third reviewer. Review quality was assessed using AMSTAR-2, and GRADE ratings were summarized according to those reported in the included reviews without repeating assessments. Results: Fifteen meta-analyses were included. Exercise-based rehabilitation was consistently associated with improvements in pain and physical function, although effect estimates varied depending on the comparison and outcome measured. Network meta-analyses also showed favorable comparative performance of knee braces and hydrotherapy for WOMAC-related outcomes; however, subgroup estimates specific to young adults with overweight were rarely reported. Self-management and psychosocial interventions showed more variable effects, with some evidence of benefits for physical activity, pain, and kinesiophobia in specific contexts. Conclusion: SMOHR may be a useful framework for organizing multiple conservative treatments for KOA, but heterogeneity and limited evidence based on age and BMI limit conclusions for young adults with overweight and early-stage disease. stages.